Fast layer-by-layer assembly of PDMS for boosting the gas separation of P84 membranes. (18th May 2022) - Li, Guozhen; Si, Zhihao; Yang, Shuai; Xue, Tanlong; Baeyens, Jan; Qin, Peiyong
Graphical abstract: Highlights: A fast PDMS layer-by-layer assembly strategy is developed to heal the defects of a P84 membrane. An ultra-short assembly time (20–30 s) of PDMS is realized by UV-curing. A faulty P84 membrane can be healed by spraying a PDMS layer at designed concentrations and cycle times. A 270% of increase in H2 /CH4 selectivity is obtained in comparison with a pristine P84 membrane. Abstract: Herein, we report an fast layer-by-layer assembly strategy via spraying method using polydimethylsiloxane (PDMS) to heal the defects of P84 membranes which are easily formed by phase inversion preparation method. The viscous PDMS is spray-atomized and uniformly adhered on the surface of the P84 membrane. An ultra-short assembly time of 20–30 s is further achieved by the UV-induced polymerization of PDMS. It is one of the fast processing time for the defects healing to date of any polymer membranes, and this fast processing time for the defects healing is a major novelty for any polymer membranes. The results demonstrate that the P84 membrane sprayed by 3 wt% of PDMS concentration and 2 of spraying cycle times has the optimum H2 separation performance, where selectivities of 232 for H2 /CH4 and 99 for H2 /N2 are 2.4 and 2.7 times higher than these of P84 membranes without healing, respectively. This strategy opens a new avenue for healing the membrane defects and fitting the requirement of producing the defect-free membranes.